Weed dynamics and productivity of wheat (Triticum aestivum) under various tillage and weed management practices - DAYAL, PARMESWAR; KUMAR, ARUN; TYAGI, SHASHANK; PAL, RAVIKESH KUMAR; MANOHAR, BAL; RANJAN, SHIVANI; SOW, SUMIT (The Indian Journal of Agricultural Sciences, 2023)
The reduced yield under conventional tillage is due to more crop-weed competition and more dry matter accumulation by the weeds (Kumar et al. 2018). Due to zero weed competition, weed-free treatments yielded the highest grain yield of all weed management practices. In contrast to this, the lowest grain yield was obtained in weedy treatment due to season-long weed competition. Maximum yield under W8 is due to broadspectrum activity of these herbicides (Sharma et al. 2014, Sunil et al. 2021). The use of zero tillage reduced weed incidence and suppression, leading to higher grain yields. Therefore, zero tillage and metsulfuron 20% wp 4 g a.i./ha + clodinafop propargyl 15% wp 60 g a.i./ha should be practiced for minimizing weed growth and maximizing the yield.